PyCO2SYS: marine carbonate system calculations in Python ... - Humphreys, Matthew P.; Gregor, Luke; Pierrot, Denis; van Heuven, Steven M. A. C.; Lewis, Ernie R.; Wallace, Douglas W. R. (Zenodo, 2020)
PyCO2SYS is a Python toolbox for solving the marine carbonate system and calculating related seawater properties. Its core is a Python implementation of CO2SYS for MATLAB. Documentation is available at PyCO2SYS.rtfd.io. Changes in v1.4.3 Bug fixes Corrected missing a pH scale conversion in SLH20 option for carbonic acid dissociation. Any calculations with this option in PyCO2SYS v1.4.1 or v1.4.2 should be updated! Validation Results validated against new release candidate version of CO2SYS-MATLAB v3. New API New wrapper function with the same input order and default gas constant option as the new CO2SYS-MATLAB v3 available in PyCO2SYS.api.CO2SYS_MATLABv3 . Internal reorganisation _approx function inputs in PyCO2SYS.solve.delta updated to match the exact Autograd functions for easier switching. ...